(untitled) (East West Medical College Journal, 2026)
Background: The prevalence of diabetes in Bangladesh is rising at an alarming rate, with projections estimating an increase from 8.4 million in 2019 to 15 million by 2045. Despite medical advances, a large proportion of patients fail to achieve adequate glycemic control, due to poor adherence to lifestyle modifications and insufficient education. To address these gaps, a digitally enabled Patient Support Program (PSP) was introduced to empower patients through structured education and hybrid counseling. Methods: A longitudinal observational study was conducted over one year with 50 insulin-treated diabetic patients. The PSP included six structured counseling sessions three telephonic consultations by physicians and three home visits by pharmacists focusing on lifestyle, diet, insulin titration, and self-monitoring of blood glucose (SMBG). Key metrics were assessed at baseline and at one year. Results: At baseline, 23% of patients achieved fasting blood sugar (FBS) control (<8 mmol/L); this increased to 73% at one year. Weekly SMBG adherence rose from 41% to 78%. Confidence in insulin titration improved significantly, with only 11% lacking confidence post-intervention compared to 61% at baseline. Overall, 87% of participants reported high satisfaction. Conclusion: The digitally enabled PSP significantly improved glycemic control, patient confidence, and adherence behaviors. This hybrid model holds promise for enhancing chronic disease management in resource-limited settings. EWMCJ Vol. 14, No. 1, January 2026: 17-20